Business informatics : navigating digital transformation with organisational semiotics - Liu, Kecheng, 1957-; Guo, Hua Claria; Li, Qi Lecky (Routledge, 2026)
The ongoing digitalisation and transformation of business requires new approaches to studying organisations. This fully revised and updated second edition provides an expert exploration of how data and information are managed through the distinctive lenses of business informatics and organisational semiotics.Reaching beyond traditional information systems theory, this book explores how meaning is constructed and how signs and digital resources influence behaviour, decision-making, and innovation. The authors employ a twin worlds concept to help readers understand the intersection between operational and digital artefacts and processes.Bridging theory and practice via a series of case studies and real-world examples, this book prepares students to understand, analyse and engage with digitally driven business environments.